2002
DOI: 10.1177/0115426502017003182
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in Predicting Resting Energy Requirements in Critically Ill Children: A Comparison of Predictive Methods to Indirect Calorimetry

Abstract: Predictive methods commonly used to estimate energy expenditure in critically ill children are very imprecise and may lead to overprovision or underprovision of nutrition support. Resting energy expenditure should be measured by indirect calorimetry whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…MEE fluctuated little during the course of admission to the PICU and most energyexpenditure measurements were below, rather than above, predicted estimates. These findings and other studies suggest that children do not become hypermetabolic while they are critically ill (5)(6)(7)(8), supporting a conservative approach, including measurement of energy expenditure, when attempting to estimate energy needs in critically ill children.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…MEE fluctuated little during the course of admission to the PICU and most energyexpenditure measurements were below, rather than above, predicted estimates. These findings and other studies suggest that children do not become hypermetabolic while they are critically ill (5)(6)(7)(8), supporting a conservative approach, including measurement of energy expenditure, when attempting to estimate energy needs in critically ill children.…”
Section: Discussionsupporting
confidence: 65%
“…Among these patients, total daily energy expenditure should be equivalent to resting energy expenditure. Recent studies have shown that critically ill children exhibited little or no elevation in metabolic rate during different phases of a critical illness (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…15,16 Postoperative cardiac infants fail to meet many criteria for accurate measures by indirect calorimetry, resulting in the use of predictive equations. 17 Predictive equations are, however, inaccurate compared with measures of energy expenditure. 3,18,19 Recently, De Wit et al 20 showed that preoperative nutrition status and cardiopulmonary bypass were associated with a greater energy expenditure following cardiac surgery and that predictive equations were clinically inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that energy requirements of paediatric patients are predicted from body weight with poor accuracy 44 45. This inaccuracy may be attributed to two principal factors: first, weight may provide a poor proxy for lean mass, and second, diseases may alter energy utilisation.…”
Section: Treatment Requirements In Patientsmentioning
confidence: 99%